Прогнозування розвитку порушень серцево-судинної системи у підлітків з патологією верхніх відділів шлунково-кишкового тракту - Крутенко, Наталія Володимирівна; Krutenko, N. V. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Дисертаційна робота присвячена питанням формування коморбідності з боку серця у підлітків з хронічною запальною патологією верхніх відділів шлунково-кишкового тракту (ШКТ). Актуальність дослідження зумовлена тим, що хвороби шлунково-кишкового тракту залишаються одними з найпоширеніших серед молодих людей, як в світі - за даними систематичного аналізу бази даних Global Burden of Diseases, так і в Україні - за даними Центру медичної статистики МОЗ щодо поширеності окремих класів хвороб серед дитячого населення з 1994 по 2016 рр., де хвороби органів травлення займали друге рангове місце серед інших дванадцяти класів. Дослідження стану здоров’я дітей на цей період продемонструвало зростання темпів приросту поширеності захворювань органів травлення на 18,6%. Сучасна патологія шлунково-кишкового тракту часто діагностується в поєднанні з іншими соматичними неінфекційними хронічними патологічними станами, серед яких одну з провідних позицій займають кардіальні порушення, що вимагає інтегрального погляду на дану проблему і комплексний підхід до діагностики та лікування.

The dissertation focuses on enhancing the methods for early diagnosis and predicting the development of heart disorders in adolescents with chronic inflammatory conditions of the upper gastrointestinal tract. The study aims to identify the prognostic factors that most significantly determine the development of cardiac syndrome, investigate the levels of cardiac-specific markers and fibrosis indices, and justifies the approaches to prevent the development of heart disorders in the context of the chronic gastrointestinal tract pathology. The purpose of the study is to improve the diagnosis of cardiovascular disorders in adolescents with chronic inflammatory pathology of the upper gastrointestinal tract (GIT) by determining informative prognostic predictors of their development based on the investigation of the regulatory and adaptive abilities of the cardiovascular system, inflammation and fibrosis indicators, and the levels of cardiac-specific markers. To achieve this goal, the following tasks were solved: to provide a clinical characteristic of the upper GIT diseases in adolescents and to study the state of the cardiovascular system in them, taking into account the variant of the lesion; to establish the level of adaptive and regulatory capabilities of the cardiovascular system in adolescents with pathology of the upper GIT; to study the level of Hypoxia-inducible 9 factor 2α (HIF-2α), High Sensitivity Cardiac Troponin I (HS-cTnI), N-terminal pro brain natriuretic peptide (NP-proBNP), C-reactive protein (CRP), Connective tissue growth factor (CTGF) and to determine prognostic signs of developing cardiovascular disorders in adolescents with pathology of the upper GIT.
Predicting the development of cardiovascular disorders in adolescents with upper gastrointestinal pathology
Науковий керівник: Шевченко Наталя Станіславівна, доктор медичних наук, професор, в.о. завідувача кафедри педіатрії, старший науковий співробітник за спеціальністю «Педіатрія»
Keywords: MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Internal medicine; підлітки; хронічний гастродуоденіт; гастроезофагеальна рефлюксна хвороба; аритмії; вегетативна дисфункція; холтерівський моніторинг; NT-proBNP; HS-cTnI; HIF-2α; кардіоспецифічні маркери; adolescents; chronic gastroduodenitis; gastroesophageal reflux disease; arrhythmias; autonomic dysfunction; Holter monitoring; cardiac-specific markers